Ending Corruption: The Interplay Among Institutional Logics, Resources, and Institutional Entrepreneurs - Misangyi, Vilmos F.; Weaver, Gary R.; Elms, Heather (Academy of Management Review, 2008)
We draw from theories of institutions and collective identities to present a threefold framework of institutional change—involving institutional logics, resources, and social actors—that furthers our understanding of the mitigation of corruption. Those social actors intent on reforming corruption function as institutional entrepreneurs, and their success depends both on articulating an anticorruption institutional logic that incorporates corruption-disabling identities, cognitive schemas, and practices and on having or developing the resources necessary to propagate the new anticorruption institutional logic.